Beyond post-traumatic stress : homefront struggles with the wars on terror - Hautzinger, Sarah J., 1963-; Scandlyn, Jean. (Walnut Creek, CA : Left Coast Press, 2014)
"When soldiers at Fort Carson were charged with a series of 14 murders, PTSD and other "invisible wounds of war" were thrown into the national spotlight. With these events as their starting point, Jean Scandlyn and Sarah Hautzinger argue for a new approach to combat stress and trauma, seeing them not just as individual medical pathologies but as fundamentally collective cultural phenomena. Their deep ethnographic research, including unusual access to affected soldiers at Fort Carson, also engaged an extended labyrinth of friends, family, communities, military culture, social services, bureaucracies, the media, and many other layers of society. Through this profound and moving book, they insist that invisible combat injuries are a social challenge demanding collective reconciliation with the post-9/11 wars"--
Machine generated contents note: IntroductionPart I: Coming Home 1. Lethal Warriors at Home 2. "Best Home Town in the Army"3. Doing Dirty Work4. PTSD = Pulling the Stigma Down 5. Decentering PTSD Part II: The Supporting Cast 6. Codeswitching : "So, why do you have frostbite?" 7. "This is Our Playground": Family Readiness Groups 8. Waiting to Serve 9. Appropriate Accommodation, or Exceptionalism for Supercitizens? 10. "This Land is Not for Sale": on Canyon and Army Expansionism Part III: Dialogue 11. "You're Not a Victim, You're a Volunteer" 12. "Closing the Gaps": Seeking Civilian-Military Dialogue 13. "Clueless Civilians" and Others 14. The Day after Veterans Day: Listening to the Homefront Conclusion: Toward a Collective Reckoning with the Post-9/11 WarsReferencesIndex.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Post-traumatic stress disorder; Post-traumatic stress disorder -- Patients -- United States; Veterans -- Mental health -- United States; Iraq War, 2003-2011 -- Psychological aspects; Afghan War, 2001- -- Psychological aspects; War on Terrorism, 2001-2009 -- Psychological aspects; Electronic books